Evaluasi Implementasi Kebijakan Asuransi Kesehatan Masyarakat Miskin (Askeskin) dan Prospek Implementasi Jaminan Kesehatan Masyarakat (Jamkesmas) - Kania Damayanti (Pusjar SKPP Lembaga Administrasi Negara, 2008)
The implementasi Askeskin (The health insurencepolicy for the poor) has increased the poor accessibility to the health services in Indonesia. The Jamkesmas’s (The health security system) programme (issued on March 2008) has been trying to solve the problem concerning the implementation of Askeskin through better participants management, transparency on financing, quality and cost control, involving the local government and service procedur.However, there are some constraints on Jamkesmas’s implementation, such as the existing of the independent verificator, the effectiveness on organizing the Jamkesmas, local government and the poor condition, as well as medical support. In order to sustain the health policy for the poor, the regulation No 40/2004: National Social Security System as a grand strategy should be followed by the regulation of The National Executing Agency, the policy of the board national Security System, the policy of Participants Management and other relevant policies Keywords:: Social Guarantee, Health Insurence, The Health Insurence Policy, Evaluation Implementation, dan Poor Society